2023
DOI: 10.1242/jcs.261094
|View full text |Cite
|
Sign up to set email alerts
|

Sec16 and Sed4 interdependently function as interaction and localization partners at ER exit sites

Abstract: COPII proteins assemble at ER exit sites (ERES) to form transport carriers. The initiation of COPII assembly in the yeast Saccharomyces cerevisiae is triggered by the ER membrane protein Sec12. Sec16, which plays a critical role in COPII organization, localizes to ERES independently of Sec12. However, the mechanism underlying Sec16 localization is poorly understood. Here, we show that a Sec12 homolog, Sed4, is concentrated at ERES and mediates ERES localization of Sec16. We found that the interaction between S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…7G). This is consistent with the finding of mutual localization between Sec16 and Sed4 40 . These observations suggest that Sed4 together with Sec16 is also involved in ERES regulation by PP1-Gip1.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…7G). This is consistent with the finding of mutual localization between Sec16 and Sed4 40 . These observations suggest that Sed4 together with Sec16 is also involved in ERES regulation by PP1-Gip1.…”
Section: Resultssupporting
confidence: 93%
“…Although TANGO1 is absent in budding yeast, development-specific regulation of Sec16 recruitment could exist. We found that the mutant of Sed4, a regulator of the Sar1 GTPase cycle and Sec16 localization to ERES 40,41 , partially phenocopied gip1 Δ, suggesting involvement of these factors in the ERES formation during meiosis.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation